Customer traffic impact on the aspects of management of fast food chain stores in Iloilo City - Alim, Clarissa; Ballescas, Rogelio, Jr; Enargan, Dale Feline; Peñalber, Rhoda
This study sought to find out the impact of customer traffic on aspects of management of fast-food chain stores in Iloilo City. The respondents of the study were 12 selected branch managers of Jollibee, McDonalds, Chowking, Greenwich, and KFC. Questionnaires in checklist form were used to gather the responses of managers. The mean, percentage, and frequency count were used as statistical tools in interpreting the data. The study revealed that customer traffic has significant relationship with the several aspects of fast-food chain store's management. These aspects were determined to be sales performance, promotional strategy, management policy, competitiveness, and budgeting.